Resin composition, pole piece, method for manufacturing same, and single battery, battery device, and power using equipment

CN122278429BActive Publication Date: 2026-10-09CHINA AVIATION LITHIUM BATTERY LUOYANG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610771411.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-09
Estimated Expiration
2046-06-01

AI Technical Summary

Technical Problem

这不仅能耗高、效率低,同时高温环境可能引发硅材料表面氧化、导电剂性能退化、电解液溶剂挥发预反应等一系列副反应,降低了电池的安全性

Benefits of technology

[0006]The resin composition provided in this application allows the polymerizable prepolymer to form the backbone of the adhesive, providing adhesion and the final network structure. The photothermal conversion material efficiently absorbs ultraviolet light and converts it into heat energy, acting as the first reaction site. The thermal initiator decomposes under the heat energy generated by the photothermal conversion material, producing free radicals and other active species that initiate the polymerization and crosslinking of the polymerizable prepolymer. The thermally conductive material is used to regulate the propagation path and rate of the reaction heat along the electrode thickness, ensuring that heat can spread smoothly and uniformly inward, avoiding localized overheating or incomplete reaction. The resin composition of this application requires only seconds of ultraviolet light irradiation to initiate the reaction during curing, and subsequent curing is propelled by its own exothermic reaction. The entire curing process requires only tens of seconds of light irradiation, with energy consumption far lower than traditional thermosetting processes. This resin composition exhibits a self-propagating reaction during reaction, allowing the polymerization reaction to proceed smoothly and ensuring uniform crosslinking density throughout the entire electrode thickness, thereby constructing a three-dimensional network with excellent mechanical properties and the ability to suppress silicon particle expansion throughout the entire area. Therefore, the resin composition of this application innovatively utilizes the principle of self-propagation to convert external energy input into internal self-sustaining chemical reaction propagation, fundamentally overcoming the bottleneck of limited penetration depth of photocuring, and can cure high-thickness electrodes at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122278429B_ABST
    Figure CN122278429B_ABST
Patent Text Reader

Abstract

The application relates to the field of batteries, and discloses a resin composition, a pole piece and a preparation method thereof, a single battery, a battery device and a power utilization equipment. The resin composition comprises a polymerizable prepolymer, a light-heat conversion material, a thermal initiator and a thermal conduction material; wherein the mass ratio of the polymerizable prepolymer, the light-heat conversion material, the thermal initiator and the thermal conduction material is 40:0.01-0.1:0.5-2:0.2-1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of batteries, and in particular to a resin composition, an electrode sheet and its preparation method, a single cell, a battery device and an electrical device. Background Technology

[0002] To significantly improve the energy density of battery cells, the industry generally adopts a strategy of increasing electrode thickness and surface loading of active materials, i.e., developing "thick electrode technology." However, the problem of huge volume expansion (>300%) of silicon-carbon materials during charge and discharge becomes particularly severe in thick electrode systems. The internal stress distribution of thick electrodes is more complex, and the cumulative effect of volume changes is stronger, which can easily lead to the failure of the overall electrode structure. This manifests as active material pulverization, conductive network damage, and large-area delamination between the electrode and the current collector, ultimately causing rapid capacity decay and the end of cycle life.

[0003] Existing binders are mainly classified into photocurable crosslinking binders and thermocurable crosslinking binders. For photocurable crosslinking binders, the crosslinking reaction can only effectively occur within a few tens of micrometers of the electrode surface. The deeper layers of the electrode remain in a state of insufficiently crosslinked linear or weakly crosslinked polymers, unable to withstand stress uniformly during cycling, making the internal regions the first weak points to fail structurally. Thermocurable crosslinking binders, when applied to thick electrodes, require deep heating curing, often exceeding 4 hours. This is not only energy-intensive and inefficient, but the high-temperature environment can also trigger a series of side reactions, such as silicon surface oxidation, conductivity degradation, and electrolyte solvent evaporation pre-reaction, reducing battery safety. Therefore, in thick electrodes, existing binders cannot yet achieve a combination of low-temperature rapid curing and deep curing. Summary of the Invention

[0004] This application discloses a resin composition, an electrode sheet and its preparation method, a single cell, a battery device and an electrical device, to achieve rapid curing and deep curing at low temperatures.

[0005] In a first aspect, this application provides a resin composition comprising: a first solvent and a polymerizable prepolymer, a photothermal conversion material, a thermal initiator, and a thermally conductive material dispersed in the first solvent; wherein the mass ratio of the polymerizable prepolymer:the photothermal conversion material:the thermal initiator:the thermally conductive material is 40:0.01~0.1:0.5~2:0.2~1.

[0006] The resin composition provided in this application allows the polymerizable prepolymer to form the backbone of the adhesive, providing adhesion and the final network structure. The photothermal conversion material efficiently absorbs ultraviolet light and converts it into heat energy, acting as the first reaction site. The thermal initiator decomposes under the heat energy generated by the photothermal conversion material, producing free radicals and other active species that initiate the polymerization and crosslinking of the polymerizable prepolymer. The thermally conductive material is used to regulate the propagation path and rate of the reaction heat along the electrode thickness, ensuring that heat can spread smoothly and uniformly inward, avoiding localized overheating or incomplete reaction. The resin composition of this application requires only seconds of ultraviolet light irradiation to initiate the reaction during curing, and subsequent curing is propelled by its own exothermic reaction. The entire curing process requires only tens of seconds of light irradiation, with energy consumption far lower than traditional thermosetting processes. This resin composition exhibits a self-propagating reaction during reaction, allowing the polymerization reaction to proceed smoothly and ensuring uniform crosslinking density throughout the entire electrode thickness, thereby constructing a three-dimensional network with excellent mechanical properties and the ability to suppress silicon particle expansion throughout the entire area. Therefore, the resin composition of this application innovatively utilizes the principle of self-propagation to convert external energy input into internal self-sustaining chemical reaction propagation, fundamentally overcoming the bottleneck of limited penetration depth of photocuring, and can cure high-thickness electrodes at low temperatures.

[0007] In a second aspect, this application provides an electrode comprising a current collector and a functional material layer coated on at least one side of the current collector, the functional material layer comprising an active substance, a conductive agent, and a binder, the binder being formed by polymerization of a resin composition of the first aspect of this application.

[0008] The electrode provided in this application has a uniform cross-linked network in the thickness direction because the binder in the functional material layer is formed by cross-linking the resin composition of the first aspect of this application. This makes the internal stress distribution of the electrode more uniform, reduces weak points under stress, and reduces the occurrence of problems such as powdering and peeling of the functional material layer, so that the electrode has a higher capacity retention rate and cycle life.

[0009] Thirdly, this application provides a method for preparing an electrode sheet, comprising: An electrode intermediate is provided, the electrode intermediate comprising a current collector and a slurry layer coated on at least one surface of the current collector, the slurry layer comprising a second solvent, an active material, a conductive agent, and a resin composition of the first aspect of this application; the second solvent contains the first solvent; The electrode intermediate is dried to remove the second solvent from the slurry layer; The dried electrode intermediate is subjected to ultraviolet light irradiation to form a functional material layer on the surface of the current collector. The irradiation time of the ultraviolet light treatment is 1s to 30s. After that, it is left to stand for 5min to 10min to complete the preparation of the electrode.

[0010] In the electrode preparation method of this application, since the slurry layer contains the resin composition of the first aspect of this application, when irradiated with ultraviolet light, the photothermal conversion material on the surface rapidly generates heat, causing the local temperature to rise to the decomposition threshold of the thermal initiator within seconds, triggering the polymerization reaction of the polymerizable prepolymer on the surface. The surface photopolymerization reaction releases additional heat of reaction, which is transferred to adjacent unreacted areas under the guidance of the heat-conducting material. The transferred heat then triggers the decomposition of the thermal initiator in that area and initiates a new polymerization reaction, and the newly generated heat of reaction continues to be transferred forward. This process proceeds spontaneously until the reaction front spreads to the entire electrode thickness, achieving deep and uniform curing. This preparation method has a short preparation time and low curing energy consumption, and can complete deep curing in a short time to obtain an electrode with stable structure, high capacity retention, and high cycle life.

[0011] Fourthly, this application provides a single-cell battery, comprising: a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein at least one of the positive electrode or the negative electrode is an electrode of the second aspect of this application.

[0012] Since at least one of the positive and negative electrode plates is an electrode plate of the second aspect of this application, the single cell of this application also has the same effect as the electrode plate of the second aspect of this application, which has high structural stability, high capacity retention and high cycle life.

[0013] Fifthly, this application provides a battery device comprising a plurality of individual cells according to the fourth aspect of this application, wherein the plurality of individual cells are connected in series and parallel.

[0014] The battery device of this application, since it includes the single cell of this application, has the same effects as the single cell of the fourth aspect of this application, which has high structural stability, high capacity retention and high cycle life.

[0015] Sixthly, this application provides an electrical device that includes a single battery as described in the fourth aspect of this application or a battery device as described in the fifth aspect of this application.

[0016] The electrical equipment of this application, since it includes the single cell or battery device of this application, has the same effects as the single cell and battery device of this application, which have high structural stability, high capacity retention and high cycle life. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the curing process in one embodiment. Detailed Implementation

[0018] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0019] It should be noted that: Unless otherwise specified, all embodiments and preferred methods mentioned herein can be combined to form new technical solutions. Unless otherwise specified, all technical features and preferred features mentioned herein can be combined to form new technical solutions. Unless otherwise specified, percentages (%) or parts refer to weight percentages or parts by weight relative to the composition. Unless otherwise specified, the components involved or their preferred components can be combined to form new technical solutions. Unless otherwise specified, the numerical range "a~b" in this application represents an abbreviation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed herein; "6~22" is merely an abbreviation of these numerical combinations. The "range" disclosed in this application can be in the form of a lower limit and an upper limit, and may be one or more lower limits and one or more upper limits, respectively. Unless otherwise specified, the various reaction or operation steps in this application can be performed sequentially or in order. Preferably, the reaction methods described herein are performed sequentially.

[0020] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to a person skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this application.

[0021] For batteries with thick electrodes, the functional material layers suffer from poor stability, making them prone to pulverization and detachment. This problem can be addressed by focusing on the binder. Taking silicon-carbon batteries as an example, in silicon-carbon anode batteries, the role of polymer binders in the silicon-carbon electrode has evolved from simple adhesion to a mechanical framework maintaining the integrity of the electrode structure. Covalent cross-linked binders, in particular, can form a three-dimensional network structure with high strength, high elastic modulus, and low swelling ratio, effectively restraining the expansion of silicon-carbon particles and providing durable interfacial adhesion. This approach has become a key research direction for solving the volume expansion problem of silicon anodes.

[0022] Existing binders are mainly classified into photocurable crosslinking binders and thermocurable crosslinking binders. For photocurable crosslinking binders, the crosslinking reaction can only effectively occur within a few tens of micrometers of the electrode surface. The deeper layers of the electrode remain in a state of insufficiently crosslinked linear or weakly crosslinked polymers, unable to withstand stress uniformly during cycling, making the internal regions the first weak points to fail structurally. Thermocurable crosslinking binders, when applied to thick electrodes, require deep heating and curing, often exceeding 4 hours. This not only results in high energy consumption and low efficiency, but the high-temperature environment can also trigger a series of side reactions, such as silicon surface oxidation, conductivity degradation, and electrolyte solvent evaporation pre-reaction, reducing battery safety.

[0023] Based on this, this application provides a resin composition that, when used as a binder in a battery, can achieve rapid low-temperature curing and deep curing through its self-propagating thermal polymerization characteristics. Specifically, the resin composition utilizes brief light exposure to initiate a surface polymerization reaction, followed by the self-propagating propagation of reaction heat initiated by specific internal components within the electrode, thereby achieving rapid and uniform deep cross-linking throughout the entire electrode thickness. When applied to high-energy-density batteries, this can significantly increase the battery's cycle life.

[0024] The resin composition of this application embodiment includes: a first solvent and a polymerizable prepolymer, a photothermal conversion material, a thermal initiator, and a thermally conductive material dispersed in the first solvent; wherein the mass ratio of the polymerizable prepolymer:the photothermal conversion material:the thermal initiator:the thermally conductive material is 40:0.01~0.1:0.5~2:0.2~1.

[0025] The resin composition provided in this application allows the polymerizable prepolymer to form the backbone of the adhesive, providing adhesion and the final network structure. The photothermal conversion material efficiently absorbs ultraviolet light and converts it into heat energy, acting as the first reaction site. The thermal initiator decomposes under the heat energy generated by the photothermal conversion material, producing free radicals and other active species that initiate the polymerization and crosslinking of the polymerizable prepolymer. The thermally conductive material is used to regulate the propagation path and rate of the reaction heat along the electrode thickness, ensuring that heat can spread smoothly and uniformly inward, avoiding localized overheating or incomplete reaction. The resin composition of this application requires only seconds of ultraviolet light irradiation to initiate the reaction during curing, and subsequent curing is propelled by its own exothermic reaction. The entire curing process requires only tens of seconds of light irradiation, with energy consumption far lower than traditional thermosetting processes. This resin composition exhibits a self-propagating reaction during reaction, allowing the polymerization reaction to proceed smoothly and ensuring uniform crosslinking density throughout the entire electrode thickness, thereby constructing a three-dimensional network with excellent mechanical properties and the ability to suppress silicon particle expansion throughout the entire area. Therefore, the resin composition of this application innovatively utilizes the principle of self-propagation to convert external energy input into internal self-sustaining chemical reaction propagation, fundamentally overcoming the bottleneck of limited penetration depth of photocuring, and can cure high-thickness electrodes at low temperatures.

[0026] The mass ratio of the polymerizable prepolymer to the photothermal conversion material is 40:0.01~0.1. If the mass ratio of the polymerizable prepolymer to the photothermal conversion material is too high, it indicates that the amount of photothermal conversion material added relative to the polymerizable prepolymer is too low, which cannot achieve effective photothermal conversion and easily leads to insufficient cross-linking reaction. If the mass ratio of the polymerizable prepolymer to the photothermal conversion material is too low, it indicates that the amount of photothermal conversion material added relative to the polymerizable prepolymer is too high. In this case, the mass proportion of the photothermal conversion material in the entire electrode is also high, which easily reduces the specific energy of the electrode.

[0027] For example, the mass ratio of the polymerizable prepolymer to the photothermal conversion material can be, for example, 40:0.01, 40:0.02, 40:0.03, 40:0.04, 40:0.05, 40:0.06, 40:0.07, 40:0.08, 40:0.09, or 40:0.1 or any two of the above values.

[0028] The mass ratio of the polymerizable prepolymer to the thermal initiator is 40:0.5~2. If the mass ratio of the polymerizable prepolymer to the thermal initiator is too high, it indicates that the amount of thermal initiator added relative to the polymerizable prepolymer is too low, resulting in low thermal initiation efficiency, which can easily reduce the reaction rate and lead to incomplete crosslinking. If the mass ratio of the polymerizable prepolymer to the thermal initiator is too low, it indicates that the amount of thermal initiator added relative to the polymerizable prepolymer is too high. In this case, the mass proportion of the thermal initiator in the entire electrode is also high, which can easily reduce the specific energy of the electrode.

[0029] For example, the mass ratio of the polymerizable prepolymer to the thermal initiator can be, for example, 40:0.5, 4:0.6, 40:0.7, 40:0.8, 40:0.9, 40:1.0, 40:1.1, 40:1.2, 40:1.3, 40:1.4, 40:1.5, 40:1.6, 40:1.7, 40:1.8, 40:1.9, or 40:2.0 or any two of the above values.

[0030] The mass ratio of the polymerizable prepolymer to the thermally conductive material is 40:0.2~1. If the mass ratio of the polymerizable prepolymer to the thermally conductive material is too high, it indicates that the amount of thermally conductive material added relative to the polymerizable prepolymer is too low, resulting in ineffective heat conduction and potentially incomplete cross-linking. If the mass ratio of the polymerizable prepolymer to the thermally conductive material is too low, it indicates that the amount of thermally conductive material added relative to the polymerizable prepolymer is too high. In this case, the mass proportion of the thermally conductive material in the entire electrode is also high, which can easily reduce the specific energy of the electrode.

[0031] For example, the mass ratio of the polymerizable prepolymer to the thermally conductive material can be, for example, 40:0.2, 40:0.3, 40:0.4, 40:0.5, 40:0.6, 40:0.7, 40:0.8, 40:0.9, or 40:1 or any two of the above values.

[0032] In one embodiment, the polymerizable prepolymer comprises a urethane group, a polymerizable group, and a hydrophilic group in its molecular structure. The urethane group is the main chain structural group of the prepolymer. The polymerizable group includes a carbon-carbon double bond and is used for polymerization. The hydrophilic group includes at least one of a carboxyl group, a sulfonic acid group, and a polyoxyethylene group. The hydrophilic group can be used to improve the dispersion uniformity of the polymerizable prepolymer in a first solvent.

[0033] In one embodiment, the room temperature viscosity of the polymerizable prepolymer is 5000 mPa·s to 60000 mPa·s. Room temperature can be, for example, 25 ± 5 °C. Excessively high viscosity of the polymerizable prepolymer will prolong the curing time or reduce the crosslinking density; excessively low viscosity will affect the molding properties of the resin composition and is detrimental to curing. Therefore, both excessively high and excessively low viscosity of the polymerizable prepolymer are unfavorable for the low-temperature crosslinking reaction, ultimately affecting the mechanical properties of the polymer obtained after polymerization.

[0034] In one embodiment, the polymerizable prepolymer has a functionality of 2 to 6. Controlling the functionality to 2 to 6 helps increase the density of the crosslinked network after crosslinking, thus improving bond strength. This level of functionality also allows the polymerized polymer to maintain low brittleness and hardness, as well as high ionic conductivity.

[0035] In one embodiment, the polymerizable prepolymer is a polyurethane acrylate.

[0036] In one embodiment, the photothermal conversion material includes at least one of carbon quantum dots, graphene oxide, carbon nanotubes, or Mxene. Mxene is a transition metal carbide, nitride, or carbonitride, and is a two-dimensional inorganic functional material. Using the above substances as photothermal conversion materials can achieve high photothermal conversion efficiency, which helps to improve the polymerization reaction rate and shorten the curing time.

[0037] In one embodiment, the thermal initiator includes at least one selected from benzoyl peroxide, azobisisobutyronitrile, dicumyl peroxide, or lauroyl peroxide. In another embodiment, the thermal initiator is benzoyl peroxide. Using benzoyl peroxide, azobisisobutyronitrile, dicumyl peroxide, or lauroyl peroxide as a thermal initiator can improve the thermal initiation efficiency. In particular, using benzoyl peroxide as a thermal initiator can significantly improve the thermal initiation efficiency.

[0038] In one embodiment, the heat-conducting material has a sheet-like structure.

[0039] In one embodiment, the heat-conducting material includes at least one of boron nitride nanosheets, boron nitride nanoparticles, alumina nanosheets, alumina nanoparticles, zinc oxide nanosheets, zinc oxide nanoparticles, silicon carbide nanosheets, or silicon carbide nanoparticles. Using boron nitride, alumina, zinc oxide, or silicon carbide nanosheets or nanoparticles as the heat-conducting material can improve heat transfer efficiency. In one embodiment, the heat-conducting material is boron nitride nanosheets. Preferably, using boron nitride nanosheets as the heat-conducting material can achieve faster heat transfer during the polymerization reaction, improving the polymerization rate and the consistency of the internal reaction.

[0040] In one embodiment, the resin composition has a solid content of 15% to 40%. Too high a solid content will affect the flowability of the composition, while too low a content will reduce the adhesive properties after polymer polymerization.

[0041] In one embodiment of this application, the first solvent is deionized water. When water is used as the first solvent, an aqueous resin composition can be obtained.

[0042] Based on the same technical objective, embodiments of this application provide an electrode. The electrode includes a current collector and a functional material layer coated on at least one surface of the current collector. The functional material layer includes an active substance, a conductive agent, and a binder, wherein the binder is formed by polymerizing the resin composition of embodiments of this application.

[0043] The electrode provided in this application has a uniform cross-linked network in the thickness direction because the binder in the functional material layer is formed by cross-linking the resin composition of the first aspect of this application. This makes the internal stress distribution of the electrode more uniform, reduces weak points under stress, and reduces the occurrence of problems such as powdering and peeling of the functional material layer, so that the electrode has a higher capacity retention rate and cycle life.

[0044] In this embodiment, the electrode can be either a positive or negative electrode. The functional material layer can be either a positive or negative electrode material layer. When the electrode is a positive electrode, the functional material layer corresponds to the positive electrode material layer. When the electrode is a negative electrode, the functional material layer is the negative electrode material layer.

[0045] In one embodiment, the electrode is a negative electrode, the current collector is a negative current collector, the functional material layer is a negative electrode material layer, and the active material includes silicon carbon material and graphite; the mass ratio of the active material: the binder: the conductive agent is 92~96:2~4:2~4.

[0046] In the negative electrode sheet, when silicon-carbon material is used as the active material, a silicon-carbon negative electrode can be formed. For the silicon-carbon negative electrode, since silicon-carbon undergoes significant volume changes during charge-discharge cycles, a binder is formed by adding the resin composition of the present application embodiment during the preparation stage. The network structure of this binder can fix the silicon-carbon material, improve the stability of the silicon-carbon material, and prevent problems such as pulverization and shedding of the silicon-carbon material during charge-discharge cycles.

[0047] In one embodiment, the mass ratio of the silicon-carbon material to the graphite is 6:4 to 9:1. Exemplarily, the mass ratio of the silicon-carbon material to the graphite can be any two values ​​between 6:4, 7:3, 8:2, or 9:1.

[0048] In one embodiment, the thickness of the functional material layer is 50 μm to 200 μm. Exemplarily, the thickness of the functional material layer may be any two values ​​between 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 150 μm, 160 μm, 180 μm, or 200 μm or more.

[0049] The resin composition of this application embodiment may include, in addition to polymerizable prepolymer, photothermal conversion material, thermal initiator and thermal conductive material, an ionic conductive agent to improve the interfacial impedance of the negative electrode in the battery and improve the rate performance of the battery.

[0050] Based on the same technical objective, embodiments of this application provide a method for preparing an electrode sheet, the method comprising: S1. An electrode intermediate is provided, the electrode intermediate comprising a current collector and a slurry layer coated on at least one surface of the current collector, the slurry layer comprising a second solvent, an active material, a conductive agent, and a resin composition according to embodiments of this application; the second solvent contains the first solvent. The second solvent, in addition to the first solvent, also includes a solvent for forming the negative electrode slurry.

[0051] S2. The electrode intermediate is dried to remove the second solvent from the slurry layer. This step mainly involves preliminary drying of the slurry layer to remove moisture and organic solvents. After drying, the resin composition has not yet undergone crosslinking.

[0052] S3. The dried electrode intermediate is subjected to ultraviolet light irradiation to form a functional material layer on the surface of the current collector. The irradiation time of the ultraviolet light irradiation is 1s~30s; then it is left to stand for 5min~10min to complete the preparation of the electrode.

[0053] In the electrode preparation method of this application, since the slurry layer contains the resin composition of the first aspect of this application, when irradiated with ultraviolet light, the photothermal conversion material on the surface rapidly generates heat, causing the local temperature to rise to the decomposition threshold of the thermal initiator within seconds, triggering the polymerization reaction of the polymerizable prepolymer on the surface. The surface photopolymerization reaction releases additional heat of reaction, which is transferred to adjacent unreacted areas under the guidance of the heat-conducting material. The transferred heat then triggers the decomposition of the thermal initiator in that area and initiates a new polymerization reaction, and the newly generated heat of reaction continues to be transferred forward. This process proceeds spontaneously until the reaction front spreads to the entire electrode thickness, achieving deep and uniform curing. This preparation method has a short preparation time and low curing energy consumption, and can complete deep curing in a short time to obtain an electrode with stable structure, high capacity retention, and high cycle life.

[0054] In one embodiment, the wavelength range of the ultraviolet light in the ultraviolet irradiation treatment is 250nm~405nm, preferably 365nm~395nm, and the ultraviolet light irradiation power is 200~1000 mW / cm². 2 The distance between the ultraviolet lamp and the electrode is 20~200mm.

[0055] In one embodiment, when the thickness of the functional material layer is 50-80 micrometers, the ultraviolet irradiation time is 1-8 seconds; when the thickness of the functional material layer is 80-120 micrometers, the ultraviolet irradiation time is 8-15 seconds; and when the thickness of the functional material layer is 120-200 micrometers, the ultraviolet irradiation time is 15-30 seconds.

[0056] Figure 1 This is a schematic diagram of the curing process structure according to one embodiment. Figure 1As shown, in one embodiment of this application, the method for preparing the negative electrode sheet includes the following steps: S1. A coating slurry is formed by mixing silicon carbon material as the negative electrode active material with the resin composition and conductive agent of the present application embodiment. The coating slurry is coated on the surface of the negative electrode current collector and pre-dried. The drying temperature can be, for example, 70°C to 100°C. S2. Expose the dried slurry layer to ultraviolet light for 1~30s. The photothermal conversion material on the surface layer generates heat rapidly, causing the local temperature to rise to the decomposition threshold of the thermal initiator within seconds, triggering the surface polymerization reaction. S3. The surface polymerization reaction releases additional heat of reaction. Guided by the heat-conducting material, it triggers the decomposition and polymerization of the thermal initiator in the unreacted area. The newly generated heat of reaction continues to be transferred forward. This process is spontaneous and the curing reaction is completed in 5-10 minutes.

[0057] Based on the same technical objective, this application provides a single-cell battery, which includes: a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein at least one of the positive electrode or the negative electrode is an electrode of this application embodiment.

[0058] In the single-cell battery of this application embodiment, since at least one of the positive electrode and the negative electrode can be an electrode of this application embodiment, the single-cell battery of this application also has the same effects as the electrode of the second aspect of this application, which has high structural stability, high capacity retention and high cycle life. In one embodiment of the battery of this application, the negative electrode is an electrode of this application embodiment.

[0059] Based on the same technical objective, this application provides a battery device, which includes a plurality of individual batteries according to this application, and the plurality of individual batteries are connected in series and parallel.

[0060] The battery device of this application embodiment, since it includes the single cell of this application, has the same effects as the single cell of this application, which has high structural stability, high capacity retention and high cycle life.

[0061] Based on the same technical purpose, embodiments of this application provide an electrical device, which includes a single battery or an electrical device according to embodiments of this application.

[0062] The electrical devices described in this application, by incorporating the individual battery cells or battery devices of this application, possess the same advantages as the individual battery cells and battery devices of this application, which exhibit high structural stability, high capacity retention, and long cycle life. The electrical devices described in this application's embodiments include, but are not limited to, electric vehicles, laptops, mobile phones, or tablet computers.

[0063] The performance of the resin composition and the corresponding battery of this application will be explained below with reference to specific embodiments.

[0064] Example 1

[0065] This embodiment describes a battery, the preparation process of which is as follows: S1. Preparation of resin composition: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0066] The above mixture was stirred at 2000 rpm for 2 hours in a planetary mixer to obtain a uniform black adhesive slurry, labeled as SM-Binder.

[0067] S2. Slurry preparation: The silicon-carbon composite (capacity approximately 1800 mAh·g) -1 Conductive carbon black (Super P) and adhesive slurry (SM-Binder) are mixed at a dry weight ratio of 94:3:3, and an appropriate amount of water is added to prepare a uniform slurry.

[0068] S3. Coating and Drying: The slurry was coated onto copper foil and dried in an oven at 80°C for 30 minutes. The coating thickness was controlled to obtain an active material surface loading of approximately 3.5 mAh cm⁻¹. -2 The electrode has a negative electrode material layer with a thickness of approximately 50 μm.

[0069] S4, Phototriggered-thermal self-propagating curing: The dried electrode sheet is passed through a conveyor belt and exposed to a 365nm UV lamp (light intensity 300 mW cm⁻¹). -2 Irradiation. For electrodes of different thicknesses, simply adjust the irradiation time (1-10 seconds) to observe a slight color change on the electrode surface (indicating the initiation of a surface reaction). After irradiation stops, the electrode interior cures on its own, with the overall curing time between 15-40 seconds.

[0070] S5. Battery assembly: The cured electrode is used as the negative electrode and assembled with the NCM811 positive electrode to form a coin cell.

[0071] Example 2-3

[0072] Examples 2-3 are examples of batteries prepared using the same method as the battery in Example 1, except that the surface loading of the active material and the thickness of the negative electrode material layer differ in step S3. In Example 2, the surface loading of the active material is approximately 5.0 mAh cm⁻¹. -2 The thickness of the negative electrode material layer is approximately 75 μm. In Example 3, the surface loading of the active material is approximately 6.5 mAh cm⁻¹. -2 The thickness of the negative electrode material layer is approximately 100 μm.

[0073] Examples 4-6

[0074] Examples 4-6 are different types of batteries, differing from Example 2 in the photothermal conversion material. In Example 4, the photothermal conversion material is graphene oxide. In Example 5, the photothermal conversion material is carbon nanotubes. In Example 6, the photothermal conversion material is a transition metal carbide, specifically Ti3C2.

[0075] Examples 7-9

[0076] Examples 7-9 are different types of batteries, differing from Example 2 in the thermal initiator. The thermal initiator in Example 7 is azobisisobutyronitrile (AIBN). The thermal initiator in Example 8 is dicumyl peroxide. The thermal initiator in Example 9 is lauroyl peroxide.

[0077] Examples 10-11

[0078] Examples 10 and 11 are different types of batteries, differing from Example 2 in the use of different heat-conducting materials. In Example 10, the heat-conducting material is aluminum oxide. In Example 11, the heat-conducting material is zinc oxide.

[0079] Example 12

[0080] Example 12 is a battery that differs from Example 2 in the amount of photothermal conversion material added to the resin composition. Specifically, 100g of an aqueous polyurethane acrylate dispersion with a solid content of 40% was taken, and 1.3g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron-sized particles and prepared as an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water were added to adjust the total solid content of the system to 25%.

[0081] Examples 13-14

[0082] Examples 13-14 are examples of batteries, differing from Example 2 in the amount of thermal initiator added to the resin composition. Details are as follows.

[0083] Example 13: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.8g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0084] Example 14: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 0.6g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0085] Example 15

[0086] Example 15 is a battery that differs from Example 2 in the amount of thermally conductive material added to the resin composition. Details are as follows.

[0087] Example 15: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.9g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0088] Comparative Examples 1-6

[0089] Comparative Examples 1-6 are different types of batteries, differing from Example 2 in that the component ratios of the resin compositions are different. Details are as follows.

[0090] Comparative Example 1: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.12g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0091] Comparative Example 2: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 2.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0092] Comparative Example 3: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 0.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0093] Comparative Example 4: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 2.5g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0094] Comparative Example 5: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 0.1g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0095] Comparative Example 6: Take 100g of waterborne polyurethane acrylate dispersion with a solid content of 40%, and add 0.8g of carbon quantum dot aqueous dispersion (solid content 5%), 1.2g of benzoyl peroxide (BPO, pre-ground into micron particles and made into an aqueous slurry), 1.5g of boron nitride nanosheets, 5g of succinic anionizer (powder, as an ion-conducting filler), and deionized water to adjust the total solid content of the system to 25%.

[0096] Comparative Example 7: Traditional UV-cured adhesive (UV-Binder)

[0097] This comparative example is a battery prepared using the same method as in Example 1. The difference lies in that its binder does not contain photothermal conversion materials or thermal initiators. It is labeled as UV-Binder.

[0098] Comparative Example 8: Commercial Adhesive (PAA)

[0099] This comparative example is a battery prepared in the same way as in Example 1. The difference is that the binder uses a 10wt% aqueous solution of polyacrylic acid (PAA, Mw=450,000) as the binder, labeled as PAA-Binder.

[0100] The specific compositions of the adhesive raw materials in Examples 1-15 and Comparative Examples 1-6 are listed in Table 1.

[0101] Table 1

[0102] The electrode strength, electrode expansion rate, and capacity retention of the negative electrode in each embodiment were tested. The test results are listed in Table 2. Table 2 also shows the curing time of the negative electrode in each embodiment.

[0103] The electrode peel strength test procedure is as follows: The silicon-carbon negative electrode sheet is cut into standard strips, 25 mm wide. High-strength adhesive tape is applied to the coated surface, with one end left unsecured for clamping. The uncoated side of the electrode sheet is fixed to a steel plate. The free end of the tape is clamped in the upper fixture of the testing machine, and the electrode substrate is clamped in the lower fixture. The peel speed is set to 50 mm / min. The test is started, and the force curve during the peel process is recorded.

[0104] The electrode expansion rate test process is as follows: After 200 cycles, the thickness change of the electrode is tested. Electrode expansion rate = (thickness in the 200th fully charged state - thickness in the constant-capacity state of the cell) / thickness in the constant-capacity state of the cell.

[0105] The battery capacity retention rate test procedure is as follows: Under an environment of 25℃±2℃, charge at a constant current and constant voltage of 0.5C to the upper limit voltage, then discharge at a constant current of 0.5C to the lower limit voltage. The average value of three tests is taken as the initial rated capacity (C0). Repeat the charge-discharge cycle (e.g., 1C charge / 1C discharge, or simulated operating current) for 200 cycles, then return to standard conditions and test the current capacity (C0) again. n Capacity retention rate = (C) n – C0) / C0×100%.

[0106] Table 2

[0107] The batteries corresponding to Examples 1-3 have different thicknesses of the negative electrode material layer in the negative electrode sheet. As the thickness of the negative electrode sheet increases, the required illumination time also increases, the electrode strength decreases slightly, the capacity retention rate after 200 cycles decreases slightly, and the electrode expansion rate increases slightly, but the overall capacity retention rate is still above 91%.

[0108] Compared with Example 2, when the photothermal conversion materials in the negative electrode are different, the electrode strength, 200-cycle capacity retention rate and electrode expansion rate of the corresponding batteries are almost unaffected.

[0109] Compared with Example 2, when the thermal initiator in the negative electrode is different, the electrode strength, capacity retention rate after 200 cycles and electrode expansion rate of the corresponding batteries change slightly. However, when the thermal initiator is benzoyl peroxide, the performance of the corresponding battery and the electrode performance will be better.

[0110] Compared with Example 2, when the thermally conductive material in the negative electrode is different, the electrode strength, capacity retention rate after 200 cycles, and electrode expansion rate of the corresponding battery change slightly in Examples 10-11. However, when the thermally conductive material is boron nitride nanosheets, the performance of the corresponding battery and electrode will be better.

[0111] Compared with Example 2, when the amount of photothermal conversion material, thermal initiator and thermal conductive material added to the negative electrode sheet is different, the electrode strength, 200-cycle capacity retention rate and electrode expansion rate of the corresponding battery change slightly, but the overall level remains high.

[0112] Compared with Example 2, when the photothermal conversion material in the negative electrode is not within the scope defined in this application, the electrode strength, 200-cycle capacity retention rate and electrode expansion rate of the corresponding battery will decrease significantly, and its performance is much lower than that of Example 2.

[0113] Compared with Example 2, when the thermal initiator in the negative electrode sheet is not within the range defined in this application, the electrode strength, 200-cycle capacity retention rate and electrode expansion rate of the corresponding battery will decrease significantly, and its performance is much lower than that of Example 2.

[0114] Compared with Example 2, when the thermally conductive material in the negative electrode is not within the range defined in this application, the electrode strength, 200-cycle capacity retention rate and electrode expansion rate of the corresponding battery will decrease significantly, and its performance is much lower than that of Example 2.

[0115] Comparative Example 7 uses a conventional binder without added photothermal conversion materials and thermal conductive materials. After 200 charge-discharge cycles, the battery's capacity retention was only about 71%, showing a significant decrease compared to Examples 1-15. Furthermore, cracks appeared inside the negative electrode.

[0116] Comparative Example 8 uses a conventional PAA binder. The corresponding battery, after 200 charge-discharge cycles, only retained about 75% of its capacity, showing a significant capacity reduction compared to Examples 1-15. Furthermore, the expansion rate of the negative electrode exceeded 200%.

[0117] As can be seen from the above tests, the battery of this application embodiment innovatively utilizes the principle of self-propagation to solidify the negative electrode sheet, converting external energy input into internal self-sustaining chemical reaction propagation, fundamentally overcoming the bottleneck of limited penetration depth of photocuring, and can solidify electrodes of theoretically arbitrary thickness.

[0118] Obviously, those skilled in the art can make various modifications and variations to the embodiments of this application without departing from the spirit and scope of this application. Therefore, if these modifications and variations of this application fall within the scope of the claims of this application and their equivalents, this application also intends to include these modifications and variations.

Claims

1. An electrode sheet, characterized in that, The device includes a current collector and a functional material layer coated on at least one surface of the current collector, the functional material layer comprising an active substance, a conductive agent, and a binder, the binder being formed by polymerization of a resin composition; The active materials include silicon carbide materials and graphite; The resin composition comprises: a first solvent and a polymerizable prepolymer, a photothermal conversion material, a thermal initiator, and a thermally conductive material dispersed in the first solvent; wherein the mass ratio of the polymerizable prepolymer:the photothermal conversion material:the thermal initiator:the thermally conductive material is 40:0.01~0.1:0.5~2:0.2~1; The mass ratio of the active substance, the binder, and the conductive agent is 92~96:2~4:2~4.

2. The electrode sheet according to claim 1, characterized in that, The molecular structure of the polymerizable prepolymer includes urethane groups, polymerizable groups, and hydrophilic groups; Polymerizable groups include carbon-carbon double bonds; The hydrophilic group includes at least one of carboxyl group, sulfonic acid group, and polyoxyethylene group.

3. The electrode sheet according to claim 1, characterized in that, The room temperature viscosity of the polymerizable prepolymer is 5000 mPa·s to 60000 mPa·s.

4. The electrode sheet according to claim 1, characterized in that, The polymerizable prepolymer has 2 to 6 functions.

5. The electrode sheet according to claim 1, characterized in that, The polymerizable prepolymer is polyurethane acrylate.

6. The electrode sheet according to any one of claims 1-5, characterized in that, The photothermal conversion material includes at least one of carbon quantum dots, graphene oxide, carbon nanotubes, or Mxene.

7. The electrode sheet according to any one of claims 1-5, characterized in that, The thermal initiator includes at least one of benzoyl peroxide, azobisisobutyronitrile, diisopropylbenzene peroxide, or lauroyl peroxide.

8. The electrode sheet according to any one of claims 1-5, characterized in that, The heat-conducting material includes at least one of boron nitride nanosheets, boron nitride nanoparticles, alumina nanosheets, alumina nanoparticles, zinc oxide nanosheets, zinc oxide nanoparticles, silicon carbide nanosheets, or silicon carbide nanoparticles.

9. The electrode sheet according to any one of claims 1-5, characterized in that, The resin composition has a solid content of 15% to 40%.

10. The electrode sheet according to any one of claims 1-5, characterized in that, The electrode is a negative electrode, and the current collector is a negative current collector.

11. The electrode according to claim 10, characterized in that, The mass ratio of the silicon-carbon material to the graphite is 6:4 to 9:

1.

12. The electrode sheet according to claim 10, characterized in that, The thickness of the functional material layer is 50μm~200μm.

13. A method for preparing an electrode sheet as described in any one of claims 1-12, characterized in that, include: An electrode intermediate is provided, the electrode intermediate comprising a current collector and a slurry layer coated on at least one surface of the current collector, the slurry layer comprising a second solvent, an active material, a conductive agent, and a resin composition used in an electrode as described in any one of claims 1-12; the second solvent contains the first solvent; The electrode intermediate is dried to remove the second solvent from the slurry layer; The dried electrode intermediate is subjected to ultraviolet light irradiation to form a functional material layer on the surface of the current collector. The irradiation time of the ultraviolet light treatment is 3s~30s; then it is left to stand for 5min~10min to complete the preparation of the electrode.

14. The preparation method according to claim 13, characterized in that, In the ultraviolet irradiation treatment, the wavelength range of the ultraviolet light is 250nm ~ 405nm, and the ultraviolet light irradiation power is 200~1000 mW / cm². 2 The distance between the ultraviolet lamp and the electrode is 20~200mm.

15. The preparation method according to claim 13, characterized in that, When the thickness of the functional material layer is 50-80 micrometers, the ultraviolet light irradiation time is 3-8 seconds; When the thickness of the functional material layer is 80-120 micrometers, the ultraviolet light irradiation time is 8-15 seconds; When the thickness of the functional material layer is 120~200 micrometers, the ultraviolet light irradiation time is 15~30s.

16. A single-cell battery, characterized in that, include: A positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein the negative electrode is an electrode as described in any one of claims 1-12.

17. A battery device, characterized in that, It includes a plurality of individual cells as described in claim 16, wherein the plurality of individual cells are connected in series and parallel.

18. An electrical appliance, characterized in that, Includes a single cell as described in claim 16 or a battery device as described in claim 17.

Citation Information

Patent Citations

  • Short-wave ultraviolet pre-crosslinking adhesive film and preparation method thereof

    CN114854314A

  • Battery pole piece as well as preparation method and application thereof

    CN118231568A